2019
DOI: 10.32737/2221-8688-2019-4-571-575
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyhydroxyesters of Sulphoimide Sakharin-6-Carbonic Acid

Abstract: Heat-resistant polyhydroxyesters were obtained through polycondensation of 2-hydroxypropyl-1,3-bis-ester of sulfoimide saccharin-6-carboxylic acid with some aliphatic diamines. Structures of the synthesized compounds were confirmed by infrared spectroscopy data. Thermal stability was studied by means of differential thermal analysis on a derivatograph of the Paulik-Paulik-Erdei system. Derivatographic studies showed that the synthesized polyhydroxyethers have a high thermal stability which decreases as a lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It was found that in the IR spectra (Figure 1) of this compound there are absorption bands in the region of 1406, 1436 cm -1 bending and in the region of 2882, 2936cm -1 of the stretching vibrations of the C-H bond of the CH 2 group; stretching vibrations of the amide C=O bond in the region of 1627 cm -1 ; stretching vibrations in the region of 1283 cm -1 C-N-bond; stretching vibrations of С-О-and О-Н-bonds of alcohol in the region of 1032 cm -1 and 3289 cm -1 ; stretching vibrations of the SO 2 bond in the region of 1245 cm -1 ; stretching vibrations of the C-O bond of the ester in the region of 1107 cm -1 ; stretching vibrations of the C=O bond of the ester in the region of 1721 cm -1 ; bending vibrations of the C-H bond (751.853 cm -1 ) of the substituted benzene ring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The synthesis of 2-hydroxypropyl-1,3-biscarboxymethylester-sulphoimide of saccharin-6-carboxylic acid was carried out according to the following scheme:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that in the IR spectra (Figure 1) of this compound there are absorption bands in the region of 1406, 1436 cm -1 bending and in the region of 2882, 2936cm -1 of the stretching vibrations of the C-H bond of the CH 2 group; stretching vibrations of the amide C=O bond in the region of 1627 cm -1 ; stretching vibrations in the region of 1283 cm -1 C-N-bond; stretching vibrations of С-О-and О-Н-bonds of alcohol in the region of 1032 cm -1 and 3289 cm -1 ; stretching vibrations of the SO 2 bond in the region of 1245 cm -1 ; stretching vibrations of the C-O bond of the ester in the region of 1107 cm -1 ; stretching vibrations of the C=O bond of the ester in the region of 1721 cm -1 ; bending vibrations of the C-H bond (751.853 cm -1 ) of the substituted benzene ring [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The synthesis of 2-hydroxypropyl-1,3-biscarboxymethylester-sulphoimide of saccharin-6-carboxylic acid was carried out according to the following scheme:…”
Section: Resultsmentioning
confidence: 99%
“…There are data in the literature that monomers with ester, acid, anhydride, amide, and hydroxyl functional groups are usually used as monomers to obtain heterocyclochain heatresistant polymers and oligomers of various structures [5][6][7][8][9][10]. Previously, we have obtained anhydride, dianhydride, and esters of sulphoimides of mono-and disaccharincarboxylic acids, which were used as monomers in the preparation of epoxyimide resins and polymeric materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with aromatic PEI, the aromatic polyestersulfoimides (PEI) have improved solubility, fire-, thermal-and radiation resistance [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike low molecular weight epoxypolymers, the high molecular weight ones are thermoplastic linear polymers with high content of the hydroxyl groups. The production of such polymers was mastered on an industrial scale in some countries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%